Use of Kahoot for teaching the english language - Puetate Medina, Edwin Emilio; Castillo Martínez, Cristhian Patricio; Méndez Ortega, Maritza Genoveva (SATHIRI, 2025)
The usual methods of teaching English have limitations, which are exacerbated by the lack of digital skills in both teachers and students, leading to poor performance in this subject across Ecuador. Therefore, the objective was to implement Kahoot in the English teaching-learning process with 331 students from the Unified General Baccalaureate of the Fiscomisional Educational Unit Hermano Miguel La Salle in Tulcán to improve their English language skills. We used a mixed and causal approach, combining field and documentary methods with a pre-experimental quasi-experimental design that included pre- and post-tests. The methodology consisted of interviewing 7 teachers and conducting surveys on Microsoft Forms and Kahoot with students to assess their English skills. We applied Kolmogorov-Smirnov as a normality test, and the results indicated that the question response distributions were not normal. Given this, we used the non-parametric Wilcoxon test to compare the pretest and posttest scores, as the number of samples exceeded 30. In conclusion, the use of Kahoot had a positive and significant impact on motivation for active participation and accessibility in learning English, as well as on competitiveness in learning English through games, but it highlights the need to train teachers to optimize its use and effectiveness in the classroom
Keywords: Kahoot; gamification; teaching; English; education